Investigating spatial and non-spatial cross-validation techniques - Kan, Kai Huai Feng (Nanyang Technological University, 2024)
Accurately evaluating predictive models, especially when built for spatial data, remains a challenge due to the limitations of traditional cross-validation techniques. While spatial cross-validation techniques have been developed to address those challenges, there is still a lack of clear guidance on when a spatial or non-spatial technique would yield the most precise and dependable assessment of a model's performance.